Unravelling the challenge of cotrimoxazole and rifampin resistance in B. melitensis and B. abortus: A systematic review and meta-analysis. - Masoumeh Beig; Elaheh Ebrahimi; Safoura Moradkasani; Forough Goodarzi; Mohammad Sholeh; Narges Golab (PLoS Neglected Tropical Diseases, 2024)
Background Brucellosis caused by Brucella (B. abortus) and Brucella melitensis (B. melitensis) poses a significant threat to human and animal populations. The World Health Organization (WHO) recommends rifampin and cotrimoxazole as first-line treatments for pediatric brucellosis. However, emerging resistance to these antibiotics raises concerns regarding their continued efficacy. This systematic review and meta-analysis aimed to quantitatively assess the prevalence of rifampin and cotrimoxazole resistance in B. abortus and B. melitensis. Methods Eligible studies were identified by systematically searching various databases, such as Scopus, PubMed, Web of Science, and EMBASE databases, using specified search terms until 18 June 2024. The inclusion criteria required studies in English to report the resistance proportion with sample size details. The meta-analysis utilized a random-effects model to assess heterogeneity using the Q-test and I2 statistic. Meta-regression and subgroup analyses explored temporal, geographical, and guideline-related variations in resistance prevalence. Results Among the 905 records, 59 studies spanning 21 countries (1976 to 2024) met the inclusion criteria. The prevalence of cotrimoxazole resistance, based on 3,756 isolates, was 0.034 (95% CI, 0.017, 0.068), with increasing trends over time, especially in B. melitensis. Rifampin resistance, involving 3,938 isolates, had a prevalence of 0.046 (95% CI, 0.027, 0.077), showing temporal and species-specific increases. Subgroup analyses revealed significant variations in resistance based on temporal, geographical, and guideline-related factors. Conclusions This systematic review and meta-analysis highlighted an alarming rise in cotrimoxazole and rifampin resistance in B. abortus and B. melitensis, particularly in pediatric brucellosis. Temporal, geographical, and species-specific variations underscore the dynamic nature of antibiotic resistance, emphasizing the need for targeted interventions, surveillance, and global collaboration to preserve the efficacy of essential antibiotics in brucellosis treatment. The limitations include potential biases and the retrospective nature of the included studies, emphasizing the urgent need for standardized surveillance methodologies and robust reporting mechanisms.